How can we celebrate Human Rights Day when young people’s needs cannot be met? (Alternate Horizons, 2022)
As Human Rights Day is commemorated, there is a need to acknowledge that even though everybody has rights, not all rights have been realized. Commemorating this day makes no sense if ordinary South Africans are still struggling to make ends meet. We, therefore, need to consider if this is the democracy that our forefathers fought for?
Keywords: human rights; youth; South Africa